Cold winter soils enhance dissolved organic carbon concentrations in soil and stream water - Haei, Mahsa; Öquist, Mats G.; Buffam, Ishi; Ågren, Anneli; Blomkvist, Peder; Bishop, Kevin; Ottosson Löfvenius, Mikaell; Laudon, Hjalmar (Geophysical research letters, 2010)
Concentrations of dissolved organic carbon ([DOC]) have increased in lakes, streams and rivers across a large part of the northern hemisphere and raised an animated scientific debate about the underlying mechanisms. The lack of consensus about the role of climate in controlling the DOC trends highlights the need for understanding the regulation of surface water DOC. We found that longer and colder winters result in higher [DOC] in a boreal headwater stream during the subsequent snowmelt. In addition, prolonged soil frost increases the spring and summer [DOC] in the riparian soil water, which is a major contributor of stream water DOC in the studied area. We conclude that winter climatic conditions can play a substantial role in controlling stream [DOC] in ways not previously understood. These findings are especially important for northern latitude regions expected to be most affected by climate change.